2017
DOI: 10.1002/tea.21401
|View full text |Cite
|
Sign up to set email alerts
|

A metasynthesis of the complementarity of culturally responsive and inquiry‐based science education in K‐12 settings: Implications for advancing equitable science teaching and learning

Abstract: Employing metasynthesis as a method, this study examined 52 empirical articles on culturally relevant and responsive science education in K‐12 settings to determine the nature and scope of complementarity between culturally responsive and inquiry‐based science practices (i.e., science and engineering practices identified in the National Research Council's Framework for K‐12 Science Education). The findings from this study indicate several areas of complementarity. Most often, the inquiry‐based practices Obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 67 publications
2
68
0
5
Order By: Relevance
“…Within the CRP in science education literature (see Brown, for a full review), sociopolitical consciousness has been largely absent and there are few examples of how science teachers engage this aspect of culturally relevant teaching. To highlight this third tenet and elaborate the nature of political clarity (Bartolome, ; Beauboeuf‐Lafontant, ) that can characterize a teacher's thoughts and actions, we draw attention to how developing students’ sociopolitical consciousness relies upon the clarity of science teachers as enacted through instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the CRP in science education literature (see Brown, for a full review), sociopolitical consciousness has been largely absent and there are few examples of how science teachers engage this aspect of culturally relevant teaching. To highlight this third tenet and elaborate the nature of political clarity (Bartolome, ; Beauboeuf‐Lafontant, ) that can characterize a teacher's thoughts and actions, we draw attention to how developing students’ sociopolitical consciousness relies upon the clarity of science teachers as enacted through instruction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A growing body of scholarship examines how preservice and inservice science teachers learn to and/or enact culturally relevant pedagogies (e.g., Adams & Laughter, 2012;Boutte, Kelly-Jackson, & Johnson, 2010;Brown, 2017;Brown & Crippen, 2016;Laughter & Adams, 2012;Madkins & Nasir, I Press;Mensah, 2011Mensah, , 2013; see Aronson & Laughter, 2016or Brown, 2017. Within this literature, there are limited empirical examples that illustrate how inservice science teachers enact CRP with attention to the intersections of race and class and science content and practices.…”
Section: Introductionmentioning
confidence: 99%
“…The PISA framework and datasets provide a wide variety of variables related to the scientific literacy performance of students. Research studies have indicated that science‐related interest, enjoyment, engagement, and self‐efficacy (Hong, Lin, Wang, Chen, & Yu, ; Jack et al, ), as well as epistemic agency (Miller, Manz, Russ, Stroupe, & Berland, ) and inquiry‐based science teaching and learning (Brown, ), have significant impacts on students' scientific literacy performance. In addition to scientific literacy, student resilience has become a favorite topic for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Student-centered instruction has been effective for increasing equity in access to technology, equity in experience, equity in gender difference, and equity among diverse student populations (Bevan, Ryoo & Shea, 2017;Brown, 2017;Buffum, Frankosky, Boyer, Wiebe, Mott, & Lester, 2016). Student-centered learning increases education equity through the integrations of social or community relevant content and allowing students to choose learning activities and ways to demonstrate knowledge (Bevan, Ryoo, & Shea, 2017;Severance, et al, 2016).…”
Section: Student-centered Learningmentioning
confidence: 99%